Bran Particle Size Influence on Pasta Microstructure, Water Distribution, and Sensory Properties. Issue 6 (2nd June 2015) - Steglich, Thomas; Bernin, Diana; Moldin, Annelie; Topgaard, Daniel; Langton, Maud
Abstract : Whole wheat pasta offers improved nutritional value compared with regular pasta but lacks appeal to many consumers owing to its negative organoleptic properties, such as texture and taste. Various approaches have been studied to improve these properties in whole wheat products. Optimizing bran particle size showed its potential in noodles, but studies of its effects in pasta are scarce. Therefore, we produced spaghetti enriched with bran fractions similar in chemical composition but with varying median particle sizes of 90, 160, 370, and 440 µm. The effect of bran particles and their median size on dried and cooked pasta was studied by light microscopy and three‐dimensional magnetic resonance imaging. In general, bran particle size did not influence the macrostructure in cooked spaghetti. However, larger bran particles created a more heterogeneous microstructure in contrast to smaller particles and affected starch granule swelling. Sensory analysis indicated a preference for pasta containing smaller particles. Our results give new insight into the microstructural features responsible for the negative consumer appeal, and they could be used to guide future efforts in designing improved pasta formulations.